2013
DOI: 10.1007/s00425-013-1887-z
|View full text |Cite
|
Sign up to set email alerts
|

Increase in ACC oxidase levels and activities during paradormancy release of leafy spurge (Euphorbia esula) buds

Abstract: The plant hormone ethylene is known to affect various developmental processes including dormancy and growth. Yet, little information is available about ethylene's role during paradormancy release in underground adventitious buds of leafy spurge. In this study, we examined changes in ethylene evolution and the ethylene biosynthetic enzyme ACC oxidase following paradormancy release (growth induction). Our results did not show an obvious increase in ethylene during bud growth. However, when buds were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Expression analysis revealed that ACOs show a high tissue specificity, with LeACO1 and LeACO2 expressed in guard cells ( Spanu et al, 1991 ). Many reports show that the silencing of ACO genes or the inhibition ACO activity reduces ethylene content in plant cells ( Chao et al, 2013 ; Satoh and Kosugi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression analysis revealed that ACOs show a high tissue specificity, with LeACO1 and LeACO2 expressed in guard cells ( Spanu et al, 1991 ). Many reports show that the silencing of ACO genes or the inhibition ACO activity reduces ethylene content in plant cells ( Chao et al, 2013 ; Satoh and Kosugi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, microarray technology works on the principle that cognate nucleic acids hybridize with each other, and it allows us to systematically evaluate the expression pattern of large subsets of genes in given tissues over multiple developmental stages and in response to various environmental stimuli (Chao et al, 2013). The focus on microarray analysis includes, but not be limited to determination of environmental factors and genetic makeup involved in adaptation and invasiveness of exotic species from the center (i.e., central populations) to its borders (i.e., marginal populations).…”
Section: Central-marginal Phenotypic and Genetic Variationmentioning
confidence: 99%
“…Considering the role of ethylene as an enhancer of fruit respiration [ 47 ], controlling its production might be essential to ensure the storage quality of fruits [ 48 , 49 ]. In previous studies, a controlled atmosphere has been widely used in postharvest preservation, showing reduced ethylene accumulation [ 50 , 51 ] by blocking its biosynthesis and absorption ( Figure 6 ) [ 52 , 53 , 54 ]. This explained the lower respiration rate for chestnuts in treated groups ( Figure 1 C), relative to CT.…”
Section: Discussionmentioning
confidence: 99%